Ghana : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2014 Article IV Consultation highlights the emergence of large fiscal and external imbalances since 2012, which has created significant challenges for Ghana. A swift return to macroeconomic stability in 2013 was thwarted by weaker external and domestic conditions. Reflecting lower gold and cocoa exports, the current account deficit exceeded 12 percent of GDP. Although recently revised estimates point to an only moderate slowdown in growth to about 7 percent, the fiscal deficit target of 9 percent of GDP was missed by about 1 percentage point. Ghana' short-term economic outlook is subject to significant risks, and growth is projected to slow to 4 3/4 percent in 2014.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet